Smart Helicopter Rotors Optimization and Piezoelectric Vibration Control - Ganguli, Ranjan; Thakkar, Dipali; Viswamurthy, Sathyamangalam Ramanarayanan; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
Exploiting the properties of piezoelectric materials to minimize vibration in rotor-blade actuators, this book demonstrates the potential of smart helicopter rotors to achieve the smoothness of ride associated with jet-engined, fixed-wing aircraft. Vibration control is effected using the concepts of trailing-edge flaps and active-twist. The authors' optimization-based approach shows the advantage of multiple trailing-edge flaps and algorithms for full-authority control of dual trailing-edge-flap actuators are presented. Hysteresis nonlinearity in piezoelectric stack actuators is highlighted and compensated by use of another algorithm. The idea of response surfaces provides for optimal placement of trailing-edge flaps. The concept of active twist involves the employment of piezoelectrically induced shear actuation in rotating beams. Shear is then demonstrated for a thin-walled aerofoil-section rotor blade under feedback-control vibration minimization. Active twist is shownto be significant in reducing vibration caused by dynamic stall. The exposition of ideas, materials and algorithms in this monograph is supported by extensive reporting of results from numerical simulations of smart helicopter rotors. This monograph will be a valuable source of reference for researchers and engineers with backgrounds in aerospace, mechanical and electrical engineering interested in smart materials and vibration control. Advances in Industrial Control aims to report and encourage the transfer of technology in control engineering. The rapid development of control technology has an impact on all areas of the control discipline. The series offers an opportunity for researchers to present an extended exposition of new work in all aspects of industrial control.
Introduction -- Mathematical Modeling -- Preliminary Studies with Active Flaps -- Flap Configuration and Control Law -- Active Flap Controller Evaluation -- Trailing-edge Flap Placement -- Piezoceramic Actuator Hysteresis -- Active Rotating Beams -- Box-beam Active Rotor Blade -- Airfoil-section Rotor Blade -- Dynamic Stall Alleviation Using Active Twist -- Appendices: Kinetic- and Strain-Energy Terms; Section Properties; Shape Functions for Space; Shape Functions for Time.
Keywords: Aerospace engineering; Astronautics; Multibody systems; Vibration; Mechanics, Applied; Optical materials; Control engineering; Aerospace Technology and Astronautics; Multibody Systems and Mechanical Vibrations; Optical Materials; Control and Systems Theory